3x+z=3y

Simple and best practice solution for 3x+z=3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+z=3y equation:


Simplifying
3x + z = 3y

Solving
3x + z = 3y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1z' to each side of the equation.
3x + z + -1z = 3y + -1z

Combine like terms: z + -1z = 0
3x + 0 = 3y + -1z
3x = 3y + -1z

Divide each side by '3'.
x = y + -0.3333333333z

Simplifying
x = y + -0.3333333333z

See similar equations:

| 4ln(7x)=20 | | -106=9k-7 | | X-y=-23 | | X-y=-27 | | 5x+5+50=90 | | 7=-3*3+2-1 | | 0.4285714285714286x+5=8 | | 5x+1=13+2x | | m^4-256=0 | | 5p-4=7 | | 35-7=3(x-2) | | 4+2+4x+3x=3x+2x+6 | | -9x-4y=1 | | 8-5x-6+9x= | | (x^(-2/3)y^(4/5)z^(3)÷(x^(1/3)y^2))^(-8/15) | | 9-4l=19 | | 12x+8x-15=0 | | (-.5x+35)=0 | | 45-20x= | | k/7-8=-10 | | 8.9=x-9.5 | | -5v-10=50 | | 8t-12=4(2t-3) | | 3x-x^2=20 | | 6i+3=-7 | | P=14*(8/t) | | -8u-15=15 | | -25t+7t^2-12=0 | | 4(n+6)-2n=3(n+3)-11 | | 7+30x=20x+23 | | 5*(4-9*2)-2*(3*2+4)+7= | | 3w^6*v^9*2v^4*7w=0 |

Equations solver categories